Case Report: resolution of refractory seizures after neurosurgical intervention in newborns with cerebral extra-axial hemorrhages - Rohaert, C.; Spoor, J. K. H.; Dremmen, M.; van Hengel-Jacobs, A. M.; Smit, L. S.; Knol, R. (Frontiers in Pediatrics, 2024)
Introduction: Intracranial hemorrhage is a significant cause of neurological damage in newborns. Extra-axial hemorrhages with intraparenchymal extension can precipitate acute clinical deterioration. Seizures are one of the presenting symptoms, which can be refractory to treatment. These hemorrhages can result in considerable long-term morbidity and mortality. Aim: The objective of this report is to present three cases of extra-axial hemorrhages in neonates, all exhibiting refractory seizures that resolved following neurosurgical intervention. Additionally, a review of literature is provided. Methods: Data collected included clinical history, laboratory findings, neuroimaging studies, type of neurosurgical intervention and patient outcome. All infants presented with extra-axial hemorrhages along with clinical and radiological signs of increased intracranial pressure within the first six days of life. These manifestations included a decreased level of consciousness, hypertension, bradycardia, and cerebral midline shift on imaging. Refractory seizures were present in all cases. Urgent magnetic resonance imaging was performed followed by neurosurgical intervention (two needle aspirations, one cranial trepanation), leading to amelioration of clinical symptoms and complete resolution of seizures. Follow-up outcomes included normal psychomotor development in one infant, mild cerebral paresis in another and delayed motor development in the third. None of the infants developed epilepsy.This study underscores the critical importance of monitoring seizure activity, conducting urgent and appropriate imaging and implementing targeted neurosurgical intervention, preferable through minimally invasive methods such as percutaneous needle aspiration. Clinicians should be aware of this clinical picture and respond promptly to mitigate neurological damage.